UPAYA MENINGKATKAN SIKAP PERCAYA DIRI MELALUI METODE ROLE PLAYING BAGI SISWA KELAS VII SMP NEGERI 3 TASIKMADU PADA SEMESTER II TAHUN PELAJARAN 2013/2014 - Surono Surono (JURNAL MITRA SWARA GANESHA, 2017)
ABSTRACT The attitude of the confident students through role playing for the students classes VII Secondary Schools 3 Tasikmadu TA. 2013-2014. This research is a research action Research design with class action model spiral of Kemmis and Taggart (1988). Source data obtained from the now confident attitude. The results of test validity and reliability 24 valid 0.810 reliability, after test then 20 statement to represent the attitude of confidence indicators. Based on the results of the findings before actions 24 students preceding actions have the attitude of self-confidence in the category of low confidence (LC), the cycle I retrieved data 11 students who haveÂ confidence attitude in category low confidance (LC) and 13 students who have confidence attitude in the category high confidance (HC) and Cycle II 24 students who have confidence attitude in the category high confidance (HC). Improved attitude of confidence before actions to the cycle I have 38 % and Cycle II experience increased 43 % compared to the cycle I. Test empirically proven effectiveness from the results of the test t, H0 is rejected which means the mean cycle II attitude confident students are high confidence categories (HC) 16.21 higher than prior to the Act, namely the attitude of self-confidence in the category of low confidence (LC) 8.17. Methods of role playing as a method that provides the same treatment, this is evidenced by the discrepancies did not mean the attitude of the confident students-sex male and female after following the method category role playing confident attitude high (high confidance/HC). The conclusions of this research are that the method of role playing effective improve the attitude of the confident grade VII Secondary Schools 3 Tasikmadu TA. 2013-2014. Â Keywords: role playing, confidence